2005
DOI: 10.1103/physrevlett.94.186101
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Characterization of a Singly Charged Oxygen Vacancy on a Single-Crystalline MgO(001) Film by Electron Paramagnetic Resonance Spectroscopy

Abstract: Electron paramagnetic resonance spectra of singly charged surface oxygen vacancies (F or color centers) formed by electron bombardment on a single-crystalline MgO film under UHV conditions are reported. The embedding of the defect in a well-defined geometrical environment allows not only for the determination of the magnetic quantities but also, in conjunction with STM studies, for the geometrical assignment of the observed signal to color centers located on the edges of the MgO film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
212
1
12

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(236 citation statements)
references
References 18 publications
(17 reference statements)
11
212
1
12
Order By: Relevance
“…STM images of similarly grown MgO(100) thin films show a high density of such sites. 45,84 Our calculations (see Figure 6) show that a Ca monomer binds to a straight step edge site with an adsorption heat of 2.1 eV (205 kJ/mol) and a charge transfer of 0.6 e. Most of this charge (68%) is transferred to the under-coordinated O atoms in the step and does not contribute to the dipole moment perpendicular to the surface. An integration of the charge difference shows this dipole perpendicular to the surface to be 2.3 D, causing an initial work function drop with slope -9.7 eV/ML, much closer to the experiment (-7 eV/ML) than Ca binding to the terrace (-14 eV/ML).…”
Section: Density Functional Theory Calculationsmentioning
confidence: 88%
See 1 more Smart Citation
“…STM images of similarly grown MgO(100) thin films show a high density of such sites. 45,84 Our calculations (see Figure 6) show that a Ca monomer binds to a straight step edge site with an adsorption heat of 2.1 eV (205 kJ/mol) and a charge transfer of 0.6 e. Most of this charge (68%) is transferred to the under-coordinated O atoms in the step and does not contribute to the dipole moment perpendicular to the surface. An integration of the charge difference shows this dipole perpendicular to the surface to be 2.3 D, causing an initial work function drop with slope -9.7 eV/ML, much closer to the experiment (-7 eV/ML) than Ca binding to the terrace (-14 eV/ML).…”
Section: Density Functional Theory Calculationsmentioning
confidence: 88%
“…Later studies on grown MgO surfaces concluded that singly charged (F+) oxygen vacancies were not present because there was no significant EPR signal detected on the pristine surface. 45 To determine if deposited Ca atoms are similarly trapped at such point defects and nucleate clusters, we calculated the binding energy of Ca at both neutral (F) and charged (F+) oxygen vacancies. Figure 5 parts c and d show that Ca binds more weakly to these defects than to the terrace.…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%
“…However, already this value is a factor of ten larger than the highest number of electrons that can be stored in paramagnetic point defects. 5 Distributing the trapped charges along the circumference of all dislocation lines, as estimated from the STM images, yields a density of 3-5 electrons per nm line defect. It should be noted that at such high carrier densities electron-electron interactions start to affect the EPR spectra, giving rise to a broadening of the resonance.…”
Section: Resultsmentioning
confidence: 99%
“…3 For example, oxygen vacancies created in an MgO surface by electron bombardment can be filled with one ͑F + ͒ or two extra electrons ͑F 0 center͒. 4,5 Electron trapping also occurs at morphological peculiarities, such as kinks and reverse corners. 6 The presence of trapped electrons strongly affects the chemical properties of oxide surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…2͑a͔͒ of these reduced TiO 2 nanobelts shows a single sharp symmetrical signal ͑g = 2.003͒ which can be attributed to singleelectron trapped on oxygen vacant sites, also known as singly occupied F + -centers. 12,13 Studies carried out on Codoped titanate nanotubes have shown the importance of this type of oxygen vacancies in mediating room temperature ferromagnetism, 2-5 with the widely accepted view of F-centers induced ferromagnetic coupling between Co 2+ via a donor impurity band exchange model. 18,19 The enlarged plot of the same graph ͑inset͒ also reveals the presence of active species trapped on Ti 3+ sites ͑g = 1.933͒ but the amount of these species is significantly smaller compared to that of the former.…”
mentioning
confidence: 99%